Implementation of Merdeka Curriculum for Sundanese and Balinese Language Subject - Ruhaliah Ruhaliah; Nunuy Nurjanah; Usep Kuswari; Ade Sutisna; Rizki Muhamad Nur (Daengku: Journal of Humanities and Social Sciences Innovation, 2024)
Education plays an important role in the development of a country. To achieve optimal educational goals, effective curriculum development is essential. In Indonesia, the introduction of the Merdeka Curriculum aims to improve the quality of learning in schools. To achieve quality learning, it is important to understand the elements of education. The elements of education include (1) students, (2) educators, (3) educational interactions between students and educators, (4) educational goals, (5) educational materials/contents (curriculum), (6) tools and methods, and (7) educational environment. The implementation of the Merdeka Curriculum in Sundanese and Balinese Language Learning is still under development. Thus, in this paper, the author intends to explain concretely how the Implementation of the Merdeka Curriculum for Sundanese and Balinese Language Subjects